A method for preparing biologically inspired high-strength and high-tenacity mineralized protein fibers

By preparing high-strength and high-strength protein fibers in a microfluidic control device, and combining post-strength and twisting treatment, the problem of inseparable fiber strength and toughness in the prior art is solved, and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-strength and high-streng Suitable for the biomedical field and has good temperature adaptability.

CN115976673BActive Publication Date: 2025-01-03ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310136390.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-01-03
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high strength and high toughness in synthetic polymer fibers, resulting in the limitation of the application of biofibers.

Method used

The microfluidic device is used to continuously prepare high-strength and high-tough protein fibers in situ. By introducing high-density non-covalent interactions with hydroxyapatite crystals into the regenerated silk fibroin matrix, the combination is stretched and twisted, and the treatment is enhanced. Mechanical properties of fibers.

Benefits of technology

It significantly improves the mechanical properties of the fibers and maintains excellent mechanical properties within the range of -50-60℃, has high temperature adaptability, and is suitable for biomedical fields such as artificial tendons and surgical sutures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115976673B_ABST
    Figure CN115976673B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a high-strength and high-toughness mineralized protein fiber inspired by biology, and belongs to the field of biological protein fiber and inorganic materials. After regenerated silk fibroin is squeezed into a microfluidic device for shear orientation, it is passed into a coagulation bath solution containing nanoscale calcium phosphate oligomers as precursors, and the calcium phosphate oligomers are hybridized with the regenerated silk fibroin solution and then dehydrated to form fibers, while the calcium phosphate oligomers grow into amorphous calcium phosphate in the fibers; then the amorphous calcium phosphate crystallizes into hydroxyapatite inside the fibers in a water environment, and non-covalent interactions are introduced between the hydroxyapatite crystals and the regenerated silk fibroin matrix, thereby enhancing the mechanical properties of the fibers, and forming primary fibers after drying; finally, after the mineralized fibers are stretched and twisted, the mechanical properties of the fibers are greatly improved. In addition, the mineralized fibers have high temperature adaptability and can maintain excellent mechanical properties even within the range of ‑50‑60°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of biological protein fibers and inorganic materials, and in particular to a method for preparing biologically inspired high-strength and high-toughness mineralized protein fibers. Background Art

[0002] High-performance biomass-based nanocomposites have attracted a great deal of scientific attention in recent years as an advanced renewable and sustainable material for structural and functional applications. Natural structural materials such as biofibers have shown extraordinary mechanical properties in evolutionary selection and have received extensive attention in biomedicine such as artificial tendons and surgical sutures.

[0003] Among natural fibers, spider silk dragline is a typical high-strength and high-tenacity protein fiber, but the supply of natural spider silk is low, which limits its wide application. Although silk has a considerable output, its mechanical properties are low and cannot meet specific needs, so its application is also limited to a certain extent.

[0004] Since natural biomineralization is a reasonable way to prepare organic-inorganic hybrid materials, biomineralization in biomimetic collagen fibers can provide a promising approach for fibrous materials. However, many inorganic materials currently cannot produce good interaction forces with organic material matrices, and even the generated hybrid materials will have partial defects that reduce their mechanical properties. Therefore, it is still a great challenge to achieve high strength and high toughness while synthesizing polymer fibers, because they are often not available at the same time, so it is difficult to obtain high-strength and high-toughness biofibers at present. Summary of the invention

[0005] In view of the deficiency that existing protein biological fibers cannot have both strength and toughness, the present invention provides a method for preparing high-strength and high-toughness mineralized protein fibers inspired by biology. High-strength and high-toughness protein fibers are continuously prepared in situ using a microfluidic device. High-density non-covalent interactions are introduced between the high-toughness regenerated silk protein matrix and the high-strength hydroxyapatite crystals, which complement each other and can greatly enhance the mechanical properties of the fibers. This method has important research value in biomedical fields such as artificial tendons and surgical sutures.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] A method for preparing biologically inspired high-strength and high-toughness mineralized protein fibers comprises the following steps:

[0008] (1) At room temperature, natural silk is degummed, dissolved, dialyzed, and concentrated to obtain a regenerated silk fibroin solution, and nano-calcium phosphate oligomers are synthesized as a precursor, and a mixed solution of ethanol and glycerol is added to form a coagulation bath;

[0009] (2) polishing the stretched capillary glass tube to prepare a microfluidic device with a tapered outlet;

[0010] (3) feeding the regenerated silk fibroin solution into the microfluidic device through a syringe pump, and after the regenerated silk fibroin solution flows through the microfluidic device and is sheared, passing into a mixed coagulation bath of ethanol and glycerol containing nano calcium phosphate oligomers, and the calcium phosphate oligomers are hybridized with the regenerated silk fibroin solution and then dehydrated to form fibers, and at the same time, the calcium phosphate oligomers grow in the fibers to become amorphous calcium phosphate, which is collected by a collecting roller I;

[0011] (4) The fibers collected by the collecting roller I are sprayed with a spray humidifier, and amorphous calcium phosphate is crystallized into hydroxyapatite inside the fibers in a water environment. Non-covalent interactions are introduced between the hydroxyapatite crystals and the regenerated silk fibroin matrix, and primary fibers are formed after drying.

[0012] Furthermore, the mass fraction of the regenerated silk fibroin solution is 20-30wt%.

[0013] Furthermore, the concentration of nano calcium phosphate oligomers in the coagulation bath is 15-30 mg / mL.

[0014] Furthermore, a post-stretching treatment step is also included, including:

[0015] (5) preparing an ethanol aqueous solution to form a stretching bath;

[0016] (6) The spun fibers described in step (4) are immersed in a stretching bath and then collected by a collecting roller II having the same diameter but different rotation speeds, wherein the angular velocities of the collecting rollers I and II are ω 1 and ω 2 , the primary fibers are subjected to 2 / ω 1 The fibers are stretched by times to form stretched fibers.

[0017] Furthermore, the method further includes the step of continuously twisting the post-stretched fibers, comprising:

[0018] (7) Setting the parameters of the twisting machine. The twisting machine consists of n conical collectors, a twisting disk, a collecting roller III, a spray humidifier and two motor drivers, one of which is used to drive the twisting disk with an angular velocity of ω. 3 , another motor driver is used to drive the collecting roller III, the linear speed is v, so the twisting density is ω 3 / 2πv;

[0019] (8) A single post-stretched fiber is wound on the conical collector, twisted by a twisting disk, and then collected by a collecting roller III. The fiber is humidified during the twisting process by the spray humidifier. The angular velocity ω of the twisting disk is adjusted.3 and the linear speed of collecting roller III is v, twisted treated fibers with different twist densities can be obtained.

[0020] Furthermore, the conical collector in the twisting machine is mounted on the twisting disk via a bearing.

[0021] Furthermore, the twisting density is 1.6-1.8 turns / mm.

[0022] Furthermore, the number of twisted strands of the twisted post-processed fiber is 4-6.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] Inspired by the biomineralization in collagen fibers, combined with microfluidic technology, nanoscale calcium phosphate oligomers are used as precursors to first form and grow into amorphous calcium phosphate in the fibers, and then crystallize into hydroxyapatite inside the primary fibers in a water environment. The high-toughness regenerated silk protein matrix and the high-strength hydroxyapatite crystals introduce high-density non-covalent interactions to enhance the mechanical properties of the fibers; after mineralized fiber post-stretching and twisting, the mechanical properties of the mineralized fibers are further improved, and they can maintain excellent mechanical properties within the range of -50-60°C, with high temperature adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the preparation of bio-inspired high-strength and high-tenacity mineralized protein fibers;

[0026] Figure 2 Schematic diagram of high-strength and high-tenacity mineralized protein fibers inspired by biological processes;

[0027] Figure 3 The phase transmission electron micrographs of calcium phosphate inorganic salts, wherein (a) is nanoscale calcium phosphate oligomers, (b) is amorphous calcium phosphate, and (c) is hydroxyapatite;

[0028] Figure 4 It is a schematic diagram of continuous post-stretching;

[0029] Figure 5 Schematic diagram of twisting, where (a) is the twisting principle diagram and (b) is the actual diagram of the twisting machine;

[0030] Figure 6 Figure 3. Changes in the mechanical properties of mineralized protein fibers generated with different concentrations of calcium phosphate oligomers, where (a) is tensile strength and Young's modulus, and (b) is tensile strain and toughness.

[0031] Figure 7 Stress-strain curves of (a) mineralized protein fiber and (b) silk protein fiber at different stretching multiples;

[0032] Figure 8 Changes in the mechanical properties of mineralized protein fibers tested in situ at different temperatures, where (a) is tensile strength and Young's modulus, and (b) is tensile strain and toughness.

[0033] Fig. 9 Figure 3 shows the changes in the mechanical properties of mineralized protein fibers under different twisting conditions, where (a) and (b) show the changes in the four mechanical properties of tensile strength, Young's modulus, tensile strain and toughness with the number of twists; (c) and (d) show the changes in the four mechanical properties of tensile strength, Young's modulus, tensile strain and toughness with the twisting density; and (e) is the simulation process of twisted fiber. DETAILED DESCRIPTION

[0034] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.

[0035] Example 1: Preparation and post-treatment of bio-inspired high-strength and high-toughness mineralized protein fibers

[0036] (1) At room temperature, natural silk is degummed, dissolved, dialyzed, and concentrated to obtain a regenerated silk fibroin solution with a mass fraction of 25 wt%, and nano-calcium phosphate oligomers are used as a precursor of the mineral phase, and a mixed solution of ethanol and glycerol in a volume fraction ratio of 4:1 is added to form a coagulation bath, and the concentration of the nano-calcium phosphate oligomers in the coagulation bath is 5, 10, 15, 20, 25, and 30 mg / mL;

[0037] (2) The stretched capillary glass tube is polished to form a conical outlet with a diameter of 180 μm, a V-shaped opening is cut on the plastic inlet of the dispensing needle, the unpolished end of the capillary glass tube is embedded in the center bottom of the dispensing needle, and epoxy resin is used to seal it on a glass slide to form a microfluidic device;

[0038] (3) As attached Figure 1 As shown, the regenerated silk fibroin solution is fed into the microfluidic device in step (2) by a syringe pump, the regenerated silk fibroin solution flows through the microfluidic device for shearing, and is passed into the ethanol and glycerol mixed coagulation bath containing calcium phosphate oligomers in step (1), the calcium phosphate oligomers and the regenerated silk fibroin solution are hybridized and dehydrated to form fibers, which are collected by a collection roller I (with a diameter of 6 cm) and sprayed with a spray humidifier for 15 minutes. As shown in the attached Figure 2 and attached Figure 3As shown, the calcium phosphate oligomers first grow into amorphous calcium phosphate in the fiber, and then crystallize into hydroxyapatite inside the fiber in a water environment. The high-toughness regenerated silk protein matrix and the high-strength hydroxyapatite crystals introduce high-density non-covalent interactions, which enhance the mechanical properties of the fiber;

[0039] (4) The fibers collected in step (3) are placed in a fume hood and dried for 12 hours to form primary fibers, and an ethanol-water solution having a volume fraction ratio of ethanol to water = 3:2 is prepared to form a stretching bath.

[0040] (5) As attached Figure 4 As shown, the spun fibers on the collection roller I after drying in step (4) are immersed in the stretching bath in step (4), and then collected by the collection roller II with the same diameter but different rotation speeds. The angular velocities of the collection roller I and the collection roller II are ω respectively. 1 and ω 2 , respectively set ω 2 :ω 1 =2, 4 and 6, 2-fold, 4-fold and 6-fold post-stretched fibers are obtained.

[0041] (6) As attached Figure 5 As shown, the twisting machine consists of n conical collectors, n bearings, a twisting disk, a collecting roller III, a spray humidifier, and two motor drivers, one of which is used to drive the twisting disk with an angular velocity of ω. 3 , another motor driver is used to drive the collecting roller III with a linear speed of v.

[0042] The conical collector and the twisting disk in the twisting machine can be connected via a bearing;

[0043] (7) The 6-fold stretched fiber in step (5) is wound on the conical collector, twisted by the twisting disk, and collected by the collecting roller III. The spray humidifier is used to humidify the fiber during the twisting process. First, keep setting 4 conical collectors, keep the linear speed of the collecting roller III v = 1.8 cm / min, and increase the angular velocity of the twisting disk ω 3 A series of twisted treated fibers with 4 twisted strands and twist densities of 1.2, 1.4, 1.6, 1.8, 2.0 and 2.2 turns / mm were obtained. Then, the linear velocity v of the collecting roller III and the angular velocity ω of the twisting disk were maintained at 1.8 cm / min. 3= 200r / min, and the number of conical collectors was increased successively to obtain twisted post-treated fibers with a twist density of 1.8 turns / mm and twisted strands of 2, 4, 6 and 8 strands.

[0044] Comparative Example 1: Preparation of silk fibroin fibers and post-treatment thereof

[0045] (1) At room temperature, natural silk is degummed, dissolved, dialyzed, and concentrated to obtain a regenerated silk fibroin solution with a mass fraction of 25 wt%, and a mixed solution of ethanol and glycerol in a volume fraction ratio of 4:1 is prepared to form a coagulation bath;

[0046] (2) The stretched capillary glass tube is polished to form a conical outlet with a diameter of 180 μm, a V-shaped opening is cut on the plastic inlet of the dispensing needle, the unpolished end of the capillary glass tube is embedded in the center bottom of the dispensing needle, and epoxy resin is used to seal it on a glass slide to form a microfluidic device;

[0047] (3) feeding the regenerated silk fibroin solution into the microfluidic device in step (2) through a syringe pump, the regenerated silk fibroin solution flows through the microfluidic device for shearing, and is passed into the coagulation bath in step (1), the regenerated silk fibroin solution is dehydrated to form fibers, and is collected by a collecting roller I (with a diameter of 6 cm);

[0048] (4) The fiber in step (3) is placed in a fume hood and dried for 12 hours to form primary fibers, and an ethanol aqueous solution with a volume fraction ratio of ethanol: water = 3:2 is prepared to form a stretching bath.

[0049] (5) The spun fibers on the collection roller I after drying in step (4) are immersed in the stretching bath in step (4), and then collected by a collection roller II with the same diameter but different rotation speeds. The angular velocities of the collection roller I and the collection roller II are ω respectively. 1 and ω 2 , respectively set ω 2 :ω 1 =2, 4 and 6, 2-fold, 4-fold and 6-fold post-stretched fibers are obtained.

[0050] Example 2: Mechanical properties test of high-strength and high-tenacity mineralized protein fibers

[0051] (1) The 6-fold post-stretched fibers obtained in step (5) of Example 1 in a coagulation bath containing different concentrations of nano-calcium phosphate oligomers were fixed on a paper frame with a test length of 1 cm, and a tensile test was performed using a universal testing machine at 25°C to obtain three stress-strain curves. The four mechanical performance indicators of tensile strength, Young's modulus, tensile strain and toughness in the stress-strain curve were extracted and averaged, as shown in the attached figure. Figure 6 As shown, it was found that within a smaller range, the concentration of the better nano calcium phosphate oligomers in the coagulation bath was 15-30 mg / mL (without special statement, the concentration of the calcium phosphate oligomers in the coagulation bath in the examples was 15 mg / mL).

[0052] (2) The spun fibers obtained in step (4) of Example 1 and the fibers obtained in step (5) after being stretched 2 times, 4 times, and 6 times were fixed on a paper frame with a test length of 1 cm, and a tensile test was performed using a universal testing machine at 25° C. to obtain three stress-strain curves, as shown in the attached figure. Figure 7 As shown in (a), the tensile strengths of the fibers obtained after initial, 2-fold, 4-fold and 6-fold stretching are 214 MPa, 405 MPa, 549 MPa and 661 MPa, respectively, and the toughness is 388 MJ / m 3 、521MJ / m 3 、243MJ / m 3 and 102MJ / m 3 .

[0053] (3) The 6-fold post-stretched fiber obtained in step (5) of Example 1 was fixed on a paper frame with a test length of 1 cm, and an in-situ tensile test was performed using a dynamic thermomechanical analyzer at -50°C, -40°C, 25°C and 60°C, respectively. The four mechanical performance indicators of tensile strength, Young's modulus, tensile strain and toughness were extracted from the three obtained stress-strain curves and the average values ​​were taken, as shown in the attached figure. Figure 8 As shown in the figure, it is found that the various mechanical properties under different temperature conditions remain basically unchanged compared with those at room temperature.

[0054] (4) The twisted post-treated fiber obtained in step (7) of Example 1 was fixed on a paper frame with a test length of 1 cm, and a tensile test was performed using a universal testing machine at 25°C to obtain three stress-strain curves. The four mechanical performance indicators of tensile strength, Young's modulus, tensile strain and toughness in the stress-strain curve were extracted and averaged, as shown in the attached figure. Fig. 9 As shown, it is found that within a smaller range, the optimal twisting conditions are 4-6 twist strands and 1.6-1.8 turns / mm of twist density.

[0055] (5) The simulation software was used to simulate the twisted post-treatment fiber with 4 twist strands and a twist density of 1.8 turns / mm to explore the effect of twisting post-treatment on the mechanical properties of the fiber. The results show that when the twisted post-treatment fiber is subjected to axial tensile load, friction is generated between the fibers due to mutual compression. The friction can be used to offset part of the load, thereby enhancing the mechanical properties of the fiber.

[0056] Comparative Example 2: Mechanical properties test of silk fibroin fiber

[0057] The spun fiber obtained in step (4) of comparative example 1 and the fibers obtained in step (5) after being stretched 2 times, 4 times and 6 times were fixed on a paper frame with a test length of 1 cm, and a tensile test was performed using a universal testing machine at 25°C to obtain three stress-strain curves, as shown in the attached figure. Figure 7 As shown in (b), the tensile strengths of the fibers obtained after initial, 2-fold, 4-fold and 6-fold stretching are 68.9 MPa, 167 MPa, 255 MPa and 345 MPa, respectively, and the toughness is 149 MJ / m 3 、260MJ / m 3 、206MJ / m 3 and 102MJ / m 3 .

[0058] By comparing Example 2 with Comparative Example 2, it is found that the strength of the fiber is greatly improved after being mineralized with inorganic calcium phosphate. And after stretching and twisting, the mechanical properties of the fiber continue to be enhanced on the original basis, and the prepared mineralized fiber also has a high temperature adaptability, and can maintain excellent mechanical properties even in the range of -50-60°C.

[0059] The above examples are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above examples, and many variations are possible. All variations that can be directly derived or associated with the contents disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing biologically inspired high-strength and high-tenacity mineralized protein fibers, characterized in that: The following steps are involved: (1) At room temperature, natural silk is degummed, dissolved, dialyzed, and concentrated to obtain a regenerated silk fibroin solution, and nano-calcium phosphate oligomers are synthesized as a precursor, and a mixed solution of ethanol and glycerol is added to form a coagulation bath; (2) polishing the stretched capillary glass tube to prepare a microfluidic device with a tapered outlet; (3) feeding the regenerated silk fibroin solution into the microfluidic device through a syringe pump, and after the regenerated silk fibroin solution flows through the microfluidic device and is sheared, passing into a mixed coagulation bath of ethanol and glycerol containing nano calcium phosphate oligomers, and the calcium phosphate oligomers are hybridized with the regenerated silk fibroin solution and then dehydrated to form fibers, and at the same time, the calcium phosphate oligomers grow in the fibers to become amorphous calcium phosphate, which is collected by a collecting roller I; (4) The fibers collected by the collecting roller I are sprayed with a spray humidifier, and amorphous calcium phosphate is crystallized into hydroxyapatite inside the fibers in a water environment. Non-covalent interactions are introduced between the hydroxyapatite crystals and the regenerated silk fibroin matrix, and primary fibers are formed after drying.

2. The method for preparing a biologically inspired high-strength and high-toughness mineralized protein fiber according to claim 1, characterized in that: The mass fraction of the regenerated silk fibroin solution is 20-30wt%.

3. The method for preparing a bio-inspired high-strength and high-toughness mineralized protein fiber according to claim 1, characterized in that: The concentration of nano calcium phosphate oligomers in the coagulation bath is 15-30 mg / mL.

4. The method for preparing a biologically inspired high-strength and high-toughness mineralized protein fiber according to claim 1, characterized in that: Also included are post-stretching processing steps, including: (5) preparing an ethanol aqueous solution to form a stretching bath; (6) The spun fibers described in step (4) are immersed in a stretching bath and then collected by a collecting roller II having the same diameter but a different rotation speed, wherein the angular velocities of the collecting rollers I and II are ω1 and ω2, respectively, and the spun fibers are stretched by a factor of ω2 / ω1 to form stretched fibers.

5. The method for preparing a bio-inspired high-strength and high-toughness mineralized protein fiber according to claim 4, characterized in that: The method further comprises the step of continuously twisting the post-drawn fibers, comprising: (7) Setting the parameters of the twisting machine, the twisting machine is composed of n conical collectors, a twisting disk, a collecting roller III, a spray humidifier and two motor drivers, one of which is used to drive the twisting disk with an angular velocity of ω3, and the other is used to drive the collecting roller III with a linear velocity of v, so the twisting density is ω3 / 2πv; (8) A single post-stretched fiber is wound on the conical collector, twisted by a twisting disk and then collected by a collecting roller III. The fiber is humidified by the spray humidifier during the twisting process. By adjusting the angular velocity ω3 of the twisting disk and the linear velocity v of the collecting roller III, twisted post-processed fibers with different twisting densities can be obtained.

6. The method for preparing a bio-inspired high-strength and high-toughness mineralized protein fiber according to claim 5, characterized in that: The conical collector in the twisting machine is mounted on the twisting disc through a bearing.

7. The method for preparing a bio-inspired high-strength and high-toughness mineralized protein fiber according to claim 5, characterized in that: The twisting density of the twisted post-processed fiber is 1.6-1.8 turns / mm.

8. The method for preparing a bio-inspired high-strength and high-toughness mineralized protein fiber according to claim 5, characterized in that: The twisted strand number of the twisted post-processed fiber is 4-6.

Citation Information

Patent Citations

  • Preparation method for linear nanometre hydroxylapatite

    CN102491298A

  • Micro-nano-scale silk fibroin induced bone mineralization calcium phosphate-based bone cement and preparation method thereof

    CN113559315A